2023
DOI: 10.1001/jamapsychiatry.2023.3416
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Association of Drug Possession Law Change With Fatal Drug Overdose in Oregon and Washington

Spruha Joshi,
Bianca D. Rivera,
Magdalena Cerdá
et al.

Abstract: ImportanceTwo states modified laws to remove or substantially reduce criminal penalties for any drug possession. The hypothesis was that removing criminal penalties for drug possession may reduce fatal drug overdoses due to reduced incarceration and increased calls for help at the scene of an overdose.ObjectiveTo evaluate whether decriminalization of drug possession in Oregon and Washington was associated with changes in either direction in fatal drug overdose rates.Design, Setting, and ParticipantsThis cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…This represents 2 years of post-intervention data, one additional year beyond the analysis period of Spencer 2023 10 and 9 months beyond that of Joshi 2023. 11 Our primary dependent variable consisted of all fatal drug poisonings (i.e., accidents, suicides, homicides, and unknown intent); the corresponding cause of death classifications are listed in the Supplement. Direct replications of Spencer 2023 used monthly-level Underlying Cause of Death mortality data restricted to unintentional drug poisonings from January 2018 to December 2021.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This represents 2 years of post-intervention data, one additional year beyond the analysis period of Spencer 2023 10 and 9 months beyond that of Joshi 2023. 11 Our primary dependent variable consisted of all fatal drug poisonings (i.e., accidents, suicides, homicides, and unknown intent); the corresponding cause of death classifications are listed in the Supplement. Direct replications of Spencer 2023 used monthly-level Underlying Cause of Death mortality data restricted to unintentional drug poisonings from January 2018 to December 2021.…”
Section: Methodsmentioning
confidence: 99%
“…As M110 took effect on February 1, 2021, we conceptualized the treatment period as commencing in the first half of 2021 or, in monthly analyses, as commencing in February 2021. Following previous studies, 10,11 we do not include Washington State in the comparison group because its supreme court effectively decriminalized drug possession for four months between February 25 (when it struck down the state’s drug possession law) and July 25, 2021, when misdemeanor recriminalization took effect.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, a study in the United States has found no evidence that legal changes to decriminalise possession of drugs have had any effect in reducing drug overdose deaths 4. Early in 2021 the states of Oregon and Washington removed or substantially reduced criminal penalties for possession of drugs and increased their spending on support services in an attempt to treat the problem as a public health issue rather than a criminal one.…”
Section: Decriminalisationmentioning
confidence: 99%
“…The Journal Impact Factor was 25.8; we send our electronic table of contents to more than 135 000 recipients each week; and users viewed or downloaded articles from our website more than 8.8 million times. Finally, you can view in the Table our articles with the highest number of views/downloads, Altmetric scores (reflecting influence in news and social media), and Web of Science citations …”
mentioning
confidence: 99%